Molecular docking and drug-likeness study of nirmatrelvir as promising drug candidates of dengue virus NS2B-NS3 protease - Huq, A.K.M. Moyeenul; Roney, Miah; Saiful Nizam, Tajuddin; Mohd Fadhlizil Fasihi, Mohd Aluwi (Marmara University, 2023)
Aedes aegypti is the primary vector for the transmission of the dengue virus (DENV), which causes dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS). There is now no antiviral medication available to treat DENV, which kills thousands of people year and infects millions of individuals. Due to the current situation, effective and useful treatments for this virus urgently need to be developed. Therefore, the goal of the current work was to determine, using molecular docking and drug-likeness analysis, the anti-viral potential of Nirmatrelvir inhibitor against DENV (1-4) NS2B-NS3 protease. Nirmatrelvir shown robust and stable bonding in the binding pocket of DENV (1-4) NS2B-NS3 protease, as demonstrated by molecular docking. According to the drug-likeness study, Nirmatrelvir shown druggability and may function as possible inhibitor to halt DENV proliferation. To establish their action and other qualities, it is also necessary to research how substances behave in both in-vitro and in-vivo settings.